Neonatal Outcome of Anemic Pregnant Mother at Private Hospital in Dhaka City (The Journal of Ad-din Women's Medical College, 2023)
Objective: This cross sectional study carried out among the anemic pregnant women to determine their neonatal outcome at a private hospital in Dhaka city.Materials and Methods: This study was conducted among 110 pregnant women after 28 weeks of gestation was selected purposively. Data were collected by interviewing the with a structured pre-tested questionnaire.Place and Period of Study: The study was conducted at Obstetrics department of the Ad-Din Barrister Rafiquil-Huq Hospital, Jurain, Dhaka and Bashundhara Ad-Din Medical College Hospital South Keranigonj, Dhaka during November 2019 to February 2020.Results: Most of the respondents (38.2%) belonged between 16-20 years age group. The mean age was 23.74±5.127 years. Almost (49.1%) up to primary & (38.2%) were up to secondary/higher secondary level. Most of the respondents were homemaker (87.3%); Monthly family income means was 19340.91±12459.647. More than one third (37.3%) of the respondents were from low income family followed by 40.9% by middle income and high income family (21.8%).  Age at marriage mean 17.79±3.400 and age at the time of first conception mean 20.12±3.173 years. Most (90.9%) of the respondents had received ANC during pregnancy. Hemoglobin level shows that 20.9% of the respondents had 10-10.9 gm/dl, 66.4% had 8-9.9 gm/dl and rest 12.7% of the respondents had 6-7.9 gm/dl.  This study reveals that 12.7% of the respondents had congenital anomaly of newborn highest 90.9% of the respondent’s fetal outcome were health & alive baby. More than half (51.8%) of the respondent’s baby were ≤ 2.5 kg birth weight and 48.2% baby were more than 2.5 kg birth weight. There was a significant relation between low birth weight (LBW) less higher education.Conclusion: All pregnant women should be given proper advice regarding their diet during pregnancy particularly on iron rich with details of foods. Dietary changes alone are not suflcient to correct an existing iron deficiency in pregnancy, and, thus, iron supplements may be necessary.The Journal of Ad-din Women's Medical College; Vol. 10 (1), Jan 2022; p 28-32